Pengaruh Budaya Nasional Terhadap Keefektifan Praktek Kompensasi di Indonesia - Naibaho, Hastuti (Universitas Muhammadiyah Yogyakarta, 2014)
The results of previous research that examines the effect of national culture on the effectiveness of human resource management practices provide empirical support that national culture affects human resource management practices. Nevertheless, the results have not been conclusive toward the degree of influence of national culture on the effectiveness of human resource management practices. It is caused that the previous studies on the influence of national culture toward human resource management practices is majority done by bundling all human resource management practices such as selection and recruitment, training, performance appraisal, compensation, and career in one study. Few studies discuss the influence of national culture on certain human resource management functions whereas national cultures specifically lead to certain human resource management functions. Therefore, it can be said that the degree of influence of national culture on human resource management practices depend on the certain functions of human resource management. This article discusses the influence of national culture on the effectiveness of the employee compensation practices in Indonesia, which will provide an important contribution to the development of compensation theory and organizational behavior to predict employee behavior. In addition, this article will also contribute to the organization as a reference to the decision in the company’s compensation plan.